A Dual-Radar Noise Compensation System for UAV-Born Cardiopulmonary Vital Signs Detection - Ishmael, Khaldoon M.; Islam, Shekh M. M.; Shadman Ishrak, Mohammad; Noor Sameera, Jannatun; Ordonez, Richard C.; Lubecke, Victor M.; Boric-Lubecke, Olga (IEEE transactions on microwave theory and techniques, 2025)
Uncrewed aerial vehicles (UAVs) equipped with Doppler radar for remote life sensing have the potential to offer an effective solution for search and rescue applications. Interference introduced by the moving UAV platform can, however, obscure human vital signs. A dual 24-GHz radar noise compensation (DRNC) system is proposed with two motion compensation methods: adaptive noise cancellation (ANC) and net signal interference cancellation (NIC). Arctangent-demodulated platform motion reference signals are used to enable accurate recovery of respiration displacement. The proposed methods have been validated with a robotic mover and a human subject, showing a motion frequency error of less than 1% and a respiration displacement error of less than 10%. The respiration displacement error was a fraction of 1 mm, even in the presence of a platform motion that exceeded 100 mm. To the best of the authors' knowledge, this is the first use of arctangent demodulation for ANC motion reference and the first UAV in-flight measurement of human respiration displacement.